Food ordering system using mobile - Nur Izzah, Zakaria (2010)
Mobile computing systems can be defined as a computing environment over physical mobility. Examples are personal digital assistants (PDAs), and mobile phone. Mobile computing systems is allows a user to perform a task from everywhere using a computing device in the public, corporate, and personal information. Nowadays, many restaurant in Malaysian still use manually, paper-based in food ordering system. The problem using manually are probability of paper lost is high and misinterpret the handwriting of order. FOSUM is design to overcome this problem. With using PDA, waiter can send the order to kitchen and cashier with fast and easier. Methodology that be used in this project is a Waterfall Model. This system will develop using Macromedia Dreamweaver 8. This system make the food ordering process easier.